Abortion in Islam: A Fiqh Examination of Medical and Social Indications - Hamdani, Muhammad Faisal; ., Ishaq (Journal of Ecohumanism, 2024)
This article aims to explore how principles of Islamic fiqh can be integrated with modern medical approaches in addressing abortion, particularly in countries with significant Muslim populations. Given the high rates of unwanted pregnancies and the grave consequences of unsafe abortions, this research is imperative to enhance understanding of the diverse fiqh perspectives regarding medical and social justifications for abortion. The methodology employed is a phenomenological qualitative approach with a constructivist paradigm, emphasising a deep comprehension of the subjective experiences and viewpoints of Islamic scholars. Data was collected through extensive literature review, including classical and contemporary fiqh texts as well as academic literature related to medical ethics in Islam. The findings reveal various interpretations of Quranic verses relevant to abortion, underscoring the importance of preserving life and human dignity. Within the context of Maqasid Shariah, it was found that abortion could be permitted in situations meeting the criteria of Darura, where the preservation of the mother's life is the paramount concern. Social phenomena related to abortion were also examined, highlighting the stigma and social consequences faced by women in Muslim communities who undergo or consider abortion. The discussion in this article includes the integration of religious law and medical practice, and the need for greater education and awareness about reproductive health within Muslim communities. This allows the research to provide clear guidelines that not only assist healthcare practitioners in making ethical decisions but also support the creation of more effective and empathetic policies that consider the health and well-being of women within a framework of human rights and social justice.